Perencanaan Peternakan dengan Konsep Eco Farming di Blitar Jawa Timur - Gunawan, Edi; Aulady, Mohamad Ferdaus Noor; Fitriyah, Dita Kamarul; Septiarsilia, Yanisfa; Pratiknyo, Yuwono Budi (Universitas Bunda Mulia, 2024)
The city of Blitar is one of the cities in the province of East Java with quite high cattle cultivation, but there are still many breeders who have not paid attention to the growth and development of their livestock because the cages are not suitable, so the meat produced is still far from the maximum word, cow kennels A good one greatly affects the growth and development of cattle, the meat produced will be more, and besides that the building life will be much longer compared to a cowshed with poor planning. From this review it becomes a parameter for researchers to plan farms with the Eco Farming concept. Farming is a concept that applies an agricultural/livestock system to re-process waste generated from these livestock activities, so as to maximize the agricultural/animal husbandry activities. than usual cows and also the planning of this farm can be an example for other cattle breeders in Blitar City. In this study, researchers used the LRFD method as a calculation of livestock steel, the final result was obtained dimensions of steel as a material for the construction of the cattle shed, namely C 125x50x20x3.2 , planning Beams with WF profile dimensions 250 X 175 X 7 X 11, Column planning with IWF profile dimensions 350 x 175 x 7 x 11.